Development of An Structural Analytic Synthetic (SAS)-Based Learning Application to Enhance Early Reading Skills in Islamic and General Primary Schools - Sunanih, Sunanih; Maulidah, Neni (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop an Android-based educational application grounded in the Structural Analytic Synthetic (SAS) approach to enhance early reading skills among first-grade students in both Islamic (Madrasah Ibtidaiyah/MI) and general (Sekolah Dasar/SD) primary schools. This research uses the Research and Development (R&D) method with the Borg and Gall’s model. The subjects of this study were grade 1 elementary school students using research instruments in the form of interviews, expert validation sheets, and initial reading test questions, while the data analysis technique used inferential statistics with the stages of normality test, homogeneity test and mean difference test. The results of the study indicate that the validation test conducted on learning media experts showed that the first test had a validation of 4.15 which is in the good category, the second test had a validation level of 5.85 which is in the very good category so that the average of tests one and two showed a validation level of 4.50 which is in the very good category. The validation test conducted on language experts showed that the first test had a validation level of 4.25 which is in the good category, the second validation test had a validation level of 4.58 which is in the very good category, while the average of the second test was a validation level of 4.41 which is in the very good category. The results confirm the SAS-based application as a viable tool to boost early literacy in first-grade students.